Librarianship in Context of Indigenous Peoples in Ukraine: Challenges, Opportunities, and Cultural Self-Determination - Sulaieva, D. (ХДАК, 2025)
Indigenous librarianship represents an emerging field within library and information science (LIS) that addresses the specific needs of Indigenous communities. This specialization promotes the preservation of Indigenous knowledge, languages, and cultural heritage while supporting these communities’ autonomy in resource management. While countries such as Canada, Australia, and New Zealand have established comprehensive frameworks supporting Indigenous knowledge systems, Ukraine remains in the early stages of implementing this concept. The nation’s rich cultural landscape encompasses Indigenous groups including the Crimean Tatars, Karaims, and Krymchaks, whose cultural heritage faces threats from historical and geopolitical challenges.
Keywords: бібліотечне обслуговування